Assets Investment and Financial Performance of Deposit Money Banks in Nigeria (2016-2021) - Odukwu Chika Victory; Eke Promise; Alafuro Elizabeth Levi; Obi Michael Ebingha; Effiong Udo Etok (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
The study uses a descriptive research approach to survey the association between asset investment and the financial health of BMBs in Nigeria. The study used time series and a secondary approach to estimate how asset investments affected deposit money institutions' financial health in Nigeria. Only six of the twenty-two (22) listed DMBs in Nigeria-United Bank for Africa (UBA), Access Bank, Unity Bank, Fidelity Bank, Eco Bank, and Zenith Bank-made up the study's population. The study was conducted from 2016 to 2021, giving us a thirty-six (36) year period of annual observation of the six DMBs that were chosen. Purposive sampling was utilized to determine the sample size. The study used secondary sources of information. The data analytic method used to ascertain the association between the independent, dependent, and moderating factors was linear regression. The study found a substantial correlation between cash equivalents, intangible assets and DMBs' return on assets in Nigeria. The same is true for property, plant, and equipment and ROA of DMBs in Nigeria. The link between asset investment and financial health of DMBs (DMBs) in Nigeria is significantly moderated by company size, which is the last factor to be discussed. Thus, the study came to the conclusion that there is a substantial correlation between asset investment and BMB financial health in Nigeria. The researchers therefore recommended that the Nigerian Central Bank ensure adequate monitoring and evaluation of banks with respect to the stipulated maximum amount a bank can invest in intangible assets, property, plant, and equipment.